Pilar-Pilar Kebijaksanaan Abadi: Menggali Filosofi dan Pandangan Hidup Bapa-Bapa Rasuli - Sostenis Nggebu; Joulanda Avni Lidya Oroh; Esther Yeti Sumiati Pratiwi; Onny Stevanus; Rahmat Jaya Gea; Anisa Takene; Tjangkar Iming (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to explain the moral values taught to the Church of Christ by the Apostolic Fathers. Through a literature review, it was found that the main principles of the teachings and way of life of the Apostolic Fathers were centered on Christ. They held firmly to apostolic dogma and accepted the authority of the Bible as the foundation of church teaching. The moral values they passed down became a model that shaped the foundation of the universal church throughout history. Figures such as Polycarp, Ignatius, Hermas, Clement, and Papias were devout church leaders who received direct guidance and the laying on of hands from the apostles of Jesus. Their steadfastness of faith often led to martyrdom, which is seen as a true confession of faith in the likeness of Christ. The spiritual heritage of the Apostolic Fathers remains relevant and can be interpreted within various cultural contexts, including the practice of church life in Indonesia. Through their exemplary lives and teachings, the Apostolic Fathers emphasized the importance of Christ-centered faith and obedience to the Scriptures. Thus, the moral values they taught continue to serve as guidelines for the church throughout all generations.